2002
DOI: 10.1074/jbc.m111883200
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide-mediated Reactive Oxygen Species and Signal Transduction in the Regulation of Interleukin-1 Gene Expression

Abstract: Lipopolysaccharide (LPS) stimulates macrophages to release inflammatory cytokines, interleukin-1␤ (IL-1), and tumor necrosis factor (TNF). LPS-induced TNF

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
358
1
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 471 publications
(394 citation statements)
references
References 70 publications
32
358
1
3
Order By: Relevance
“…It has also been reported that p38 and ERK pathways play an important role in IL-1b and TNF-a production, respectively (Hsu and Wen 2002;Shi et al 2002). Herein, our data demonstrate that all three types of MAPKs are activated in cisplatin-treated cells.…”
Section: Fig 10supporting
confidence: 76%
“…It has also been reported that p38 and ERK pathways play an important role in IL-1b and TNF-a production, respectively (Hsu and Wen 2002;Shi et al 2002). Herein, our data demonstrate that all three types of MAPKs are activated in cisplatin-treated cells.…”
Section: Fig 10supporting
confidence: 76%
“…For example, it has been reported that the p38 and ERK pathways play an important role in IL-1β and TNF-α production, respectively (Hsu and Wen 2002;Shi et al 2002). Therefore, we speculated that modulation of other signaling events involving MAPKs by flunarizine might affect the activation of NF-κB by cisplatin and consequently attenuate pro-inflammatory cytokine production and apoptotic cell death after cisplatin exposure.…”
Section: Discussionmentioning
confidence: 99%
“…a protein) produced by targeted cells and passed on through the medium or the induction of a (secondary) bystander signal in the Mechanisms of bystander cH2AX foci induction S Burdak-Rothkamm et al bystander cells themselves. As some cytokines can be induced by increased ROS levels (Bellocq et al, 1999;Ayache et al, 2002;Hsu and Wen, 2002;Kosmidou et al, 2002;Hwang et al, 2004;Ryan et al, 2004), they are likely candidates for a secondary bystander signal. Furthermore, some of these cytokines (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of soluble factors like reactive oxygen species (ROS) (Azzam et al, 2002;Shao et al, 2003aShao et al, , 2005, nitric oxide (NO) (Shao et al, 2003b(Shao et al, , 2005Sokolov et al, 2005) and cytokines released from irradiated cells as well as gap junction intercellular communication (Azzam et al, 2001;Shao et al, 2003a;Mitchell et al, 2004;Sokolov et al, 2005) have recently been reported. Most interestingly, several cytokines can be induced by ROS and NO/NOS (Ayache et al, 2002;Hsu and Wen, 2002;Kosmidou et al, 2002;Hwang et al, 2004;Ryan et al, 2004) providing a possible link between different factors potentially involved in bystander signalling. End points used for the study of bystander effects in vitro have included micronuclei formation (Azzam et al, 2002;Kashino et al, 2004;Shao et al, 2004), gene mutations and genomic instability (Zhou et al, 2000), gene expression changes (Azzam et al, 2002;Yang et al, 2005), transformation (Sawant et al, 2001), proliferation (Gerashchenko and Howell, 2003), cell survival, apoptosis (Belyakov et al, 2002;Lyng et al, 2002), cell cycle arrest (Azzam et al, 2000) and most recently the induction of gH2AX foci in bystander cells (Hu et al, 2005;Sokolov et al, 2005;Yang et al, 2005).…”
Section: Introductionmentioning
confidence: 99%